The problem of content in the theory of formal operations: Piaget and Vygotskii in the South African context - Moll, Ian (My University, 1984)
This thesis explores the extent to which Piaget falsely ignores the socio-economic contents of cognition in his account of formal operational thought. His biological conception of the origins of knowledge leads him to emphasize the structures of cognition, but Vygotskii's dialectical materialist psychology challenges this. It denies Piaget's separation of content from structure and accuses him of losing sight of the social construction of cognition. The thesis attempts to clarify the resultant dispute (drawing particularly on Buck-Morss' charge that Piaget has a socio-economic bias) and goes on to examine a concrete instance of the problem in the attainment of formal operations across different South African communities. Piaget's tasks showed that rural children exhibit significantly less formal operational ability than their urban peers and that within the latter group, township children have less abstract cognitive ability than their middle-class counterparts. Interviews showed that these tendencies correspond in each case to more emphasis on concrete activities, and less on abstract activities, in the everyday lifestyle of the former grouping. But this is in itself not enough to demonstrate a weakness in Piaget's theory. On a more abstract level, the final part of the thesis argues that the epistemology of genetic epistemology is ·inadequate because it leaves the very social nature of knowledge out of the picture. Taken together with concrete cross-cultural differences, this establishes a serious problem of content - a social "blindness'' - in Piaget's theory of formal operations.
A Dissertation Submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts in Psychology.
Keywords: COGNITION IN CHILDREN--SOUTH AFRICA.